427How does childhood maltreatment influence cardiovascular disease? A sequential causal mediation analysis. (2nd September 2021) - Soares, Ana Goncalves; Howe, Laura D; Hammerton, Gemma; Heron, Jon; Rich-Edwards, Janet; Magnus, Maria C; Halligan, Sarah L; Fraser, Abigail
Abstract: Background: Childhood maltreatment (CM) has been associated with cardiovascular disease (CVD), but the mechanisms of this relationship are not fully understood. We explored the relative contribution of anxiety/depression, smoking, body mass index (BMI) and C-reactive protein (CRP) to the association between CM and CVD in the United Kingdom (UK) and whether this differed by sex and type of maltreatment. Methods: We used data from 40, 596 men and 59, 511 women from UK Biobank. To estimate the indirect effects of CM (physical, sexual and emotional abuse, and emotional and physical neglect) on incident CVD, we applied a sequential mediation approach using g-computation. Results: Together anxiety/depression, smoking, BMI and CRP mediated 26%-90% of the association between CM and CVD, and the contribution of these mediators differed by type of maltreatment and sex. For sexual abuse, emotional abuse and emotional neglect, anxiety/depression was the most important mediator (accounting for 16%-43% of the total effect), especially in women. In men, BMI contributed the most in associations of physical abuse and physical neglect with CVD; in women anxiety/depression and BMI had similar contributions. Conclusions: These findings add to the understanding of how CM affects CVD and highlight the potential to reduce the burden of CVD in people exposed to CM through targeting modifiable mediating factors. Key messages: Anxiety/depression, smoking, BMI and inflammation mediated part of the association between CM and CVD, and the contribution of these mediators differed by type of maltreatment and sex.